Steel Wire Mechanical Property Degradation Study Based on Numerical Simulation - Jiangjiang Li; Xuanyu Zhang (Advances in Materials Science and Engineering)
With the rapid development of underground engineering construction, such as deep mining of mineral resources and tunnel excavation under complex geological conditions, the existing support methods cannot meet the deformation requirements. It is necessary to conduct in-depth research on the stress status and damage evolution of the hanger rods, to establish a theoretical basis for the design principles and criteria of key components. In this paper, the degradation law of the mechanical properties of the hanger steel wire with the degree of corrosion is analyzed in detail. The results show that the corrosion changes the geometry of the cross section of the steel wire, which leads to the degradation of the mechanical properties of the steel wire. With the increase of corrosion length and depth, the strength, stiffness, and ultimate strain of the steel wire are reduced to varying degrees, and the effect of pitting corrosion is more significant than that of uniform corrosion. The closer the holes are, the greater the corrosion effect is.